A RARE CASE OF AGGRESSIVE CALCITONIN-NEGATIVE MEDULLARY THYROID CARCINOMA - Loh, Ee Wen; Tan, Florence Hui Sieng (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Medullary thyroid carcinoma (MTC), accounting for 5% of thyroid cancers, is a neuroendocrine tumour derived from parafollicular C-cells of the thyroid gland. MTC secretes calcitonin which is used as the gold standard biomarker for diagnosis and monitoring. Calcitonin-negative MTC (CNMTC) is rare with less than 80 cases reported in the literature. CASE We report a case of CNMTC presenting with aggressive clinical course. A 70-year-old female presented to the emergency department with a 2-day history of odynophagia, dyspnea and aphonia. She reported progressive worsening of neck swelling, dysphonia and dysphagia over the past 2 months. Examination revealed a hard right anterior neck mass (12 x 5 cm). She was treated for impending airway obstruction with intravenous dexamethasone and awake fiberoptic intubation. Neck CT scan showed 5.7 x 5.5 x 9.9 cm right thyroid mass with 5.2 x 4.0 x 6.5 cm matted cervical lymphadenopathy causing tracheal compression, right internal jugular vein and sternocleidomastoid muscle infiltration, right brachiocephalic artery and common carotid artery encasement. Metastatic work-up revealed liver metastases. Excisional biopsy of the thyroid mass reported malignant cells with CKAE1/AE3, CD56, synaptophysin and TTF-1 positivity suggestive of medullary thyroid carcinoma, awaiting further immunohistochemistry (IHC) staining with calcitonin. Thyroid function, serum calcium and carcinoembryonic antigen (CEA) level 1.41 ng/mL (N <5.0) were normal. Serum calcitonin was not available. Following tumour debulking and tracheostomy, histopathological examination showed high grade neuroendocrine tumour with Ki67 proliferation index >90%. Tumour IHC were negative for calcitonin and leucocyte common antigen (LCA). A final diagnosis of CNMTC was made. Patient refused further therapy and succumbed to her illness soon after. CONCLUSION CNMTC poses both diagnostic and management challenge due to its non-secretory state and the lack of guidelines on treatment and prognostication. Past literature reviews had shown variable clinical progress. The lack of calcitonin and CEA elevations further complicate post-operative surveillance.